In Silico Structure Analysis of Type 2 Diabetes Associated Toll Like Receptor-4 (TLR4): Insights into the structure and function of Type 2 diabetes associated Toll-like receptor 4 (Journal of Advances and Scholarly Researches in Allied Education, 2018)
TLRs are evolutionary conserved Pattern-Recognition Receptors (PRRs) that play a key role in the activation of innate immune response by recognizing highly conserved pathogen-associated molecular patterns (PAMPs), such as the Lipopolysaccharide (LPS) component of gram-negative bacteria. The role of TLR4 genes are associated with type 2 diabetes mellitus in several populations. In this paper modeller was used for homology modelling of human TLR4 (O00206.2). The TLR4 Human Md-2-E.Coli (3FXI) and crystal structure of Mouse TLR4md-2 (3VQ1) were selected as a template for homology modelling. Ramachandram plot of TLR4 (O00206.2) has 81.2 residue in the most favored region, while template TLR4 (3FXI) has 69.1 and template TLR4 (3VQI) has 77.8 in the most favored region. 3-D structure validation of TLR4 was done by RAMPAGE and SAVES tools. 3D structure of Human TLR4 suggested the active site remains conserved among family members and the major interaction are similar to those observed for the homologous templates.